The Influence 0f Work Environment and Organizational Citizenship Behavior (OCB) on The Work Motivation of Employees of The Secretariat Division at The Halal Product Assurance Agency (BPJPH) - Romli; Fatahillah, Irfan; Afrizal (CV ODIS, 2025)
The purpose of this study is to ascertain how the Halal Product Guarantee Agency's (BPJPH) Secretariat Division employees' work motivation is impacted by their work environment and organizational citizenship behavior (OCB). Questionnaires are used to gather data for the quantitative approach, which has a descriptive and causal design approach. SPSS version 26 is used for testing. The study's findings demonstrated that employee work motivation is positively and significantly impacted by the work environment and organizational citizenship behavior (OCB).